2020
DOI: 10.1177/0284185120901507
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of talonavicular injection using ultrasound versus anatomical landmark: a cadaver study

Abstract: Background Intra-articular injections have diagnostic and therapeutic roles in foot and ankle pathologies due to complex anatomy, small size, diverse bones, and joints with proximity in this region. Conventionally, these injections are carried out using anatomical landmark technique and/or fluoroscopic guidance. The small joint space and needle size make the injection challenging. Fluoroscopy is not readily available in the clinical setting; ultrasound-guidance for injections is therefore increasingly being us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The use of US or fluoroscopy significantly improved the accuracy of injections into the tarsometatarsal joints [ 55 ]. A cadaveric study on talonavicular joint injection accuracy showed that the needle was correctly positioned in all US-guided injections, while it was misplaced in all cases of blind injections [ 57 ]. In juvenile idiopathic arthritis patients with ankle synovitis, image-guided intra-articular corticosteroid injections resulted in longer remission time when compared with palpation guidance [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of US or fluoroscopy significantly improved the accuracy of injections into the tarsometatarsal joints [ 55 ]. A cadaveric study on talonavicular joint injection accuracy showed that the needle was correctly positioned in all US-guided injections, while it was misplaced in all cases of blind injections [ 57 ]. In juvenile idiopathic arthritis patients with ankle synovitis, image-guided intra-articular corticosteroid injections resulted in longer remission time when compared with palpation guidance [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The limited studies in the literature on TNJ and CCJ IAI accuracy also show improved results with ultrasound guidance. Jha et al, in a cadaveric study on TNJ IAI, found that all ultrasound-guided injections were successful, while all palpation-guided injections were unsuccessful [ 68 ]. Reach et al found the accuracy rates of TNJ and CCJ blind IAIs to be 50% and 60%, respectively [ 61 ].…”
Section: Lower Extremitymentioning
confidence: 99%
“…In several studies, ultrasonographic guidance has been found to be comparable to the criterion standard fluoroscopic guidance. 37,42,66 Platelet-rich plasma (PRP) injections have been considered a promising treatment for ankle (tibiotalar) OA. 56 The high interest is driven by the strong safety profile of PRP and promising results in the knee.…”
Section: Daniel M Cushman Mdmentioning
confidence: 99%
“…In several studies, ultrasonographic guidance has been found to be comparable to the criterion standard fluoroscopic guidance. 37,42,66…”
Section: Diagnostic and Therapeutic Value Of Injectionsmentioning
confidence: 99%